2011
DOI: 10.1111/j.1464-410x.2011.10376.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation (RFA) therapy for renal angiomyolipoma (AML): an alternative to angio‐embolization and nephron‐sparing surgery

Abstract: What ' s known on the subject? and What does the study add? The natural history of renal angiomyolipomas (AML) shows increasing size and increasing risk of haemorrhage. For those patients undergoing treatment, extirpative surgery or renal angio-embolization has increased morbidity. Due to its haemostatic effect, radio-frequency ablation (RFA) may be used safely and effectively for the treatment of small ( < 4 cm), symptomatic renal AML.This study represents the largest case series reporting on RFA for renal AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…Prior to 1976, more than 90% of sporadic AMLs were treated with total nephrectomy, as a malignant lesion could not be excluded (48). With improvement of cross sectional imaging and even in cases of low-fat tumors, AMLs can now be confidently diagnosed with an MRI specificity of up to 99% (52,53 (25)(26)(27)36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to 1976, more than 90% of sporadic AMLs were treated with total nephrectomy, as a malignant lesion could not be excluded (48). With improvement of cross sectional imaging and even in cases of low-fat tumors, AMLs can now be confidently diagnosed with an MRI specificity of up to 99% (52,53 (25)(26)(27)36).…”
Section: Discussionmentioning
confidence: 99%
“…During an 11-year study period, 23 patients underwent SAE in emergency to treat bleeding AMLs (n=6) (Figure 2) or as prophylactic treatment for high-risk AMLs (tumor size >4 cm, abnormal vasculature on CT, other symptoms) (n=17) and could be followedup. One small sporadic asymptomatic AML was not embolized because its feeding vessels could not be identified during the arteriography; a percutaneous radiofrequency ablation was performed instead (48,49). We preferred a conservative approach by active surveillance for a second sporadic asymptomatic AML because of its very small angiomyomatous component.…”
Section: Figurementioning
confidence: 99%
“…No recurrence has been observed for this technique, especially in case of small tumors (8). There have been 3 large case series, where ablation therapies were used for the treatment of a subtype of AMLs including 15 patients with intraoperative biopsy confirmed renal AML, 280 cases with small renal masses, and 7 with pathologically confirmed renal AML; the results revealed that ablative techniques are safe, efficient, and minimally invasive for the treatment of AMLs (43). However, using cryoablation for large AMLs is associated with some retroperitoneal bleeding, which may occur during the treatment (8).…”
Section: Treatmentmentioning
confidence: 99%
“…However, using cryoablation for large AMLs is associated with some retroperitoneal bleeding, which may occur during the treatment (8). Moreover, it may be associated with some postoperative complications such as those related to the procedure, that is, transient hematuria and intercostals nerve transection, or those related to the surgery (i.e., myocardial infarction and pneumonia) (43). As for borderline surgical candidates, it has been shown that each considerable change in the postcontrast-enhanced imaging probability of a benign or indolent lesion allows surgery to be suspended and is more likely to impact the pursuit of biopsy, active surveillance, or percutaneous ablative therapy (44).…”
Section: Treatmentmentioning
confidence: 99%
“…15 More recently, several small case series have investigated the role of radiofrequency ablation (RFA), however little long term follow-up is available. 16,17 Current treatment strategies are twofold. In patients with active retroperitoneal hemorrhage, or with a symptomatic angiomyolipoma, intervention is widely advocated.…”
Section: Current Management Strategies Of Angiomyolipomamentioning
confidence: 99%